Selection of Trichoderma mutants with enhanced cellulase production and resistant to catabolite repression - Szakacs G; Megyeri L; Kovacs K; Zacchi G (浙江大学学报. 农业与生命科学版)
Due to high cost and relatively low efficiency of cellulase enzymes used for the saccharification of pretreated lignocelluloses, the improvement of cellulase secreting microorganisms is of vital importance. Trichoderma reesei QM 6a, an excellent source of cellulase was selected in the late 1960's at Natick Laboratories by its performance on pure cellulose (Solka Floc, Avicel). QM 6a is the wild parent strain of best existing hypercellulolytic mutants such as Rut C30, VTT-D-80133, L27, CL-847 and others. Utilization of cheaper carbon sources (e.g., pretreated wood or straw) both in enzyme production and in hydrolysis necessitates to investigate fungal species other than T. reesei.A screening program was initiated to test 150 wild-type Trichoderma strains in shake flask for cellulase production on SO2-impregnated and steam pretreated spruce and willow, candidate substrates for bioalcohol program in Sweden. Filter paper activity (FPA) method was used to determine the overall cellulase activity. Strain TUB F-1505 was selected as promising candidate for mutagenesis. This wild strain was isolated from a tropical rain forest area near Manaus, Brazil. Isolate F-1505 was subjected to NTG-mutation to select catabolite (glucose, glycerol) resistant mutants. A Petri plate clearing assay using Walseth cellulose, glycerol or glucose and Triton X100 (colony size inhibitor) was applied for pre-screening of the colonies. Over 6000 colonies were evaluated. Best colonies were tested in shake flask fermentation on pretreated spruce and willow as carbon sources. Mutants producing higher levels of cellulase (FPA) were further mutated by either NTG or UV-light. At least 4 mutants were obtained and freeze-dried exhibiting equivalent or higher cellulase production as compared to Trichoderma reesei Rut C30.